The Impact of Visual Marketing on Purchasing Behavior in E-Commerce: A Case Study in The Fashion Industry - Agus Marwan; H. Harkim; Bambang Sugiharto (Golden Ratio of Data in Summary, 2024)
This study explores the impact of visual marketing elements on consumer purchasing behavior within the fashion e-commerce industry, focusing on visual aesthetics, user-generated content (UGC), and influencer endorsements. Using a qualitative approach, semi-structured interviews were conducted with 25 participants to capture in-depth insights into how visual cues shape consumer perceptions, build trust, and influence purchase intentions. Thematic analysis of the data revealed three main findings: high-quality visuals evoke emotional responses that increase product appeal, UGC serves as a crucial factor in establishing trust and reducing purchase hesitation, and influencer endorsements significantly impact consumer decision-making by adding perceived value and trend relevance. These findings contribute to existing theories, such as the Stimulus-Organism-Response (S-O-R) model, by illustrating the diverse ways in which visual stimuli influence consumer behavior on emotional, social, and practical levels. Managerial implications include the strategic use of high-quality visuals, encouragement of UGC, and selection of authentic influencers to enhance consumer engagement and conversion. This study provides a comprehensive understanding of how visual marketing shapes consumer behavior in fashion e-commerce, offering valuable insights for both academic research and practical applications in the digital marketplace.